Asthma: beyond the prescription - Partridge, Martyn (Henry Stewart Talks, 2011)
Patient/health professional contact, The role of the asthma patients, Denial of the diagnosis, Knowledge of asthma amongst the parents, Levels of asthma control, How patients perceive their asthma, Treatment guidelines, Assessing patients' preferences, Defining the ideal relationship with a specialist, Involvement in treatment decisions, British asthma guidelines, Compliance of practices with recommendations, Written asthma action plans, Software, Literacy and health, The use of technology, Sources of information, Better compliance with electronic reminders, Use of non technological adjuncts, Consultation is important for patients
Reviewed at 2022/04/12